Intranasal ketamine as a treatment for psychiatric complications of long COVID: A case report - Baldwin Kaitlyn PharmD; Wanson Annabelle MD, FRCPC; Gilecki Lee-Anne MD, FRCPC; Dalton Courtney BSP; Peters Evyn MD, FRCPC; Halpape Katelyn BSP, ACPR, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Background Neuropsychiatric symptoms associated with long COVID are a growing concern. A proposed pathophysiology is increased inflammatory mediators. There is evidence that typical serotonergic antidepressants have limited efficacy in the presence of inflammation. Although ketamine has shown promise in MDD, there is limited evidence supporting the use of ketamine to treat depressive symptoms associated with long COVID. Case Report This case took place on an inpatient psychiatry unit in a Canadian hospital. The patient was admitted with a 10-month history of worsening depression and suicidality following infection with COVID-19. Depressive symptoms and suicidal ideation were assessed throughout treatment using the Montgomery-Asberg Depression Rating Scale (MADRS). Written informed consent was obtained prior to data collection. This patient received 4 doses of intranasal ketamine which resulted in rapid improvement of depressive symptoms and complete resolution of suicidality with no major adverse events. Discussion There is evidence to support long COVID symptoms result from dysregulated inflammatory processes. The presence of inflammation in patients with MDD has correlated to poor outcomes with first-line antidepressants. It has been demonstrated that IV ketamine is associated with decreased inflammatory mediators and proportional decrease in depressive symptoms. Conclusions Intranasal ketamine in this case was effective at treating depressive symptoms and suicidal ideation associated with long COVID. This is consistent with available data that demonstrates ketamine's efficacy in reducing inflammatory mediators associated with neuropsychiatric symptoms. Therefore, ketamine may be a potential therapeutic option to treat long COVID and persistent depressive symptoms.